Carbon dioxide evolution from snow-covered agricultural ecosystems in Finland - Koizumi, Hiroshi; Kontturi, Markku; Mariko, Shigeru; Mela, Timo (Agricultural Research Centre of Finland, 1996)
Hiilidioksidin vapautumista lumipeitteisestä ja paljaasta maasta mitattiin suorasti ja epäsuorasti Suomen maaperästä. Mittaukset tehtiin turve-, hiekka- ja savimaasta. Suorissa mittauksissa käytettiin suljetun kammion menetelmää ja epäsuorissa Fickin diffuusiomallia. Kaikkien em. maalajien talvilämpötila vaihteli 2 cm:n syvyydessä Oja +1 °C välillä. Hiilidioksidipitoisuus lumikerroksen sisällä oli sitä korkeampi mitä paksumpi lumikerros oli. Lumen hiilidioksidipitoisuudesta mitattu keskimääräinen hiilidioksidivirtaus vaihteli 10-27 mg CO2 m-2 h-1 diffuusiomallilla ja 18-27 mg CO2m-2 h-1 suljetun kammion menetelmällä mitattuna. Tämän tutkimuksen mukaan lumi on hyvä maan lämpöeriste, ja CO2:n tuotanto jatkuu maassa lämpö-tilojen pysyessä lumipeitteen alla jäätymispisteen yläpuolella. Maaperästä vapautuu ilmakehään hiilidioksidia lumipeitteen läpi. Hiilidioksidin muodostumista talvella ja kesällä kuvaavan suhdeluvun arvioitiin olevan noin 4 %. Täten merkittävä osa vuotuisista hiilidioksidipäästöistä syntyy talvella.

The release of CO2 from the snow surface in winter and the soil surface in summer was directly or indirectly measured in three different soil types (peat, sand and clay) in agricultural ecosystems in Finland. The closed chamber (CC) method was used for the direct and Fick's diffusion model (DM) method for the indirect measurements. The winter soil temperatures at 2-cm depth were between 0 and 1°C for each soil type. The concentration of CO2 within the snowpack increased linearly with snow depth. The average fluxes of CO2 calculated from the gradients of CO2 concentration in the snow using the DM method ranged from 10 to 27 mg CO2 m2 h -1 and with the CC method from 18 to 27 mg CO2 m -2 h -1. These results suggest that the snow insulates the soil thermally, allowing CO2 production to continue at soil temperatures slightly above freezing in the winter. Carbon dioxide formed in the soil can move across the snowpack up to the atmosphere. The winter/summer ratio of CO2 evolution was estimated to exceed 4%. Therefore, the snow-covered crop soil served as a source of CO2 in winter, and CO2 evolution constitutes an important part of the annual CO2 budget in snowy regions.
Keywords: hiilidioksidi; closed chamber method; CO2 flux; CO2 profile; heavy clay soil; peat soil; sand soil; snowpack; soil respiration; subarctic climate region